Dampak Green Marketing dan Green Brand Image terhadap Keputusan Pembelian pada Konsumen Laki-laki Produk Fashion Ramah Lingkungan Merk X di Kediri - Palupi, Shara Merry; Putranti, Ellyn Citra (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The research conducted has the intention and purpose of providing references regarding the impact of green marketing and green brand image on purchasing decisions of male consumers of environmentally friendly fashion products brand X in Kediri. This study uses a quantitative approach with multiple linear regression analysis data analysis techniques. The population of the study was 103 consumers of environmentally friendly fashion products brand X in Kediri, the sampling technique used purposive sampling which applied several criteria to produce a sample of 63 people. The results of the study indicate that green marketing and green brand image have an impact on purchasing decisions of male consumers of environmentally friendly fashion products brand X in Kediri, both partially and simultaneously. The conclusions drawn from this study indicate that male consumers have logical characteristics, where they are considered more loyal to products that suit their needs and desires. In addition, male consumers tend to prefer recycled fashion products that are more environmentally friendly, in addition to being aware and caring about the environment, also because these products have their own uniqueness so that they can be said to be anti-mainstream products.